Qualitative study of attitude and efficacy of first year students to early clinical exposure in ultrasound and orthopedics - Bijwe, Anand D.; Bijwe, Smita A.; Hassan, Sameeullah B. A.; Pokale, Minoti S.; Vidhale, Deepali G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Traditional Indian medical education limits first-year MBBS students to classroom settings, delaying clinical exposure until the second year. Early clinical exposure (ECE) aims to integrate basic sciences with clinical practice, enhancing student understanding and interest through direct patient interaction. Aim was to assess first-year MBBS students' perceptions of ECE. Objectives were to introduce clinical settings to first-year students, and to explore students' experiences and attitudes towards ECE. Methods: The study was conducted at Dr. Panjabrao Deshmukh Memorial Medical College, Amravati, involving 100 first-year MBBS students. Ethical clearance and permissions were obtained. Students participated in bedside teaching in small groups over four weeks, focusing on clinical conditions and diagnostics. Observations in the radiology department included first-trimester ultrasounds with patient interaction. A qualitative approach using focus group discussions and a post-test questionnaire was employed. Results: Learning and knowledge: 81% found ECE helpful, interest in topic: 75% reported increased interest, motivation: 84% felt motivated to learn more, correlation with clinical features: 60% found it helpful, ward rounds: 89% valued participation, knowledge sharing: 87% appreciated discussion opportunities, and overall utility: 79% recognized ECE's utility. Feedback indicated significant enhancements in learning, interest, and motivation, despite some neutral or negative responses. Conclusions: ECE is a vital teaching tool that improves first-year MBBS students' understanding, motivation, and professional skills. Despite logistical challenges, its overall positive impact on medical education justifies its implementation.